CD14hiCD16+ monocytes phagocytose antibody-opsonised Plasmodium falciparum infected erythrocytes more efficiently than other monocyte subsets, and require CD16 and complement to do so. Issue 1 (December 2015) - Zhou, Jingling; Feng, Gaoqian; Beeson, James; Hogarth, P.; Rogerson, Stephen; Yan, Yan; Jaworowski, Anthony
Abstract Background With more than 600, 000 deaths from malaria, mainly of children under five years old and caused by infection withPlasmodium falciparum, comes an urgent need for an effective anti-malaria vaccine. Limited details on the mechanisms of protective immunity are a barrier to vaccine development. Antibodies play an important role in immunity to malaria and monocytes are key effectors in antibody-mediated protection by phagocytosing antibody-opsonised infected erythrocytes (IE). Eliciting antibodies that enhance phagocytosis of IE is therefore an important potential component of an effective vaccine, requiring robust assays to determine the ability of elicited antibodies to stimulate thisin vivo . The mechanisms by which monocytes ingest IE and the nature of the monocytes which do so are unknown. Methods Purified trophozoite-stageP. falciparum IE were stained with ethidium bromide, opsonised with anti-erythrocyte antibodies and incubated with fresh whole blood. Phagocytosis of IE and TNF production by individual monocyte subsets was measured by flow cytometry. Ingestion of IE was confirmed by imaging flow cytometry. Results CD14hi CD16+ monocytes phagocytosed antibody-opsonised IE and produced TNF more efficiently than CD14hi CD16- and CD14lo CD16+ monocytes. Blocking experiments showed that Fcγ receptor IIIa (CD16) but not Fcγ receptor IIa (CD32a) or Fcγ receptor I (CD64) was necessary for phagocytosis. CD14hi CD16+ monocytes ingested antibody-opsonised IE when peripheral blood mononuclear cells were reconstituted with autologous serum but not heat-inactivated autologous serum. Antibody-opsonised IE were rapidly opsonised with complement component C3 in serum (t1/2 = 2-3 minutes) and phagocytosis of antibody-opsonised IE was inhibited in a dose-dependent manner by an inhibitor of C3 activation, compstatin. Compared to other monocyte subsets, CD14hi CD16+ monocytes expressed the highest levels of complement receptor 4 (CD11c) and activated complement receptor 3 (CD11b) subunits. Conclusions We show a special role for CD14hi CD16+ monocytes in phagocytosing opsonisedP. falciparum IE and production of TNF. While ingestion was mediated by Fcγ receptor IIIa, this receptor was not sufficient to allow phagocytosis; despite opsonisation with antibody, phagocytosis of IE also required complement opsonisation. Assays which measure the ability of vaccines to elicit a protective antibody response toP. falciparum should consider their ability to promote phagocytosis and fix complement.